Anti-biofilm Activities from Bergenia crassifolia Leaves against Streptococcus mutans - Liu, Yucui; Xu, Yanjie; Song, Qiuhang; Wang, Fei; Sun, Luguo; Liu, Lei; Yang, Xiaoguang; Yi, Jingwen; Bao, Yongli; Ma, Haifeng; Huang, Honglan; Yu, Chunlei; et al. (Frontiers in Microbiology, 2017)
Streptococcus mutans has been reported as a primary cariogenic pathogen associated with dental caries. The bacteria can produce glucosyltransferases (Gtfs) to synthesize extracellular polysaccharides (EPSs) that are known as virulence factors for adherence and formation of biofilms. Therefore, an ideal inhibitor for dental caries is one that can inhibit planktonic bacteria growth and prevent biofilm formation. Bergenia crassifolia (L.), widely used as a folk medicine and tea beverage, has been reported to have a variety of bioactivities. The present study aimed to explore the effect of B. crassifolia (L.) leaf extracts on the biofilm of Streptococcus mutans. The B. crassifolia (L.) leaf extracts showed inhibitory effects by decreasing viability of bacteria within the biofilm, as evidenced by the XTT assay, live/dead staining assay and LDH activity assay, and could decrease the adherence property of S. mutans through inhibiting Gtfs to synthesize EPSs. In addition, the reduced quantity of EPSs and the inhibition of Gtfs were positively correlated with concentrations of test samples. Finally, the MTT assay showed that the extracts had no cytotoxicity against normal oral cells. In conclusion, the extracts and sub-extracts of B. crassifolia leaves were found to be antimicrobial and could reduce EPS synthesis by inhibiting activities of Gtfs to prevent bacterial adhesion and biofilm formation. Therefore, B. crassifolia leaves have potential to be developed as a drug to prevent and cure dental caries.